2021
DOI: 10.1053/j.gastro.2021.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antibiotic Resistance Genes in Gut Microbiome of Patients With Cirrhosis

Abstract: BACKGROUND AND AIMS: Cirrhosis is associated with changes in intestinal microbiota that can lead to hepatic encephalopathy (HE) and infections, especially with antibioticresistant organisms. However, the impact of gut microbial antibiotic resistance gene (ARG) burden on clinical outcomes is unclear. The aims of the study were to determine the impact of ARGs in cirrhosis-related gut metagenome on outcomes and disease progression, study the effect of rifaximin on ARG burden, and compare ARGs in cirrhosis with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 60 publications
1
42
0
Order By: Relevance
“…These findings are interesting because, in addition to the prior studies showing altered metabolomics and antibiotic resistance genes, the higher prevalence of VF-containing bacteria likely reflect a hostile gut microbiome in cirrhosis. 51 , 52 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are interesting because, in addition to the prior studies showing altered metabolomics and antibiotic resistance genes, the higher prevalence of VF-containing bacteria likely reflect a hostile gut microbiome in cirrhosis. 51 , 52 …”
Section: Discussionmentioning
confidence: 99%
“…Whether these VF-expressing bacteria are a marker of poor prognosis, such as those with antibiotic resistance genes or whether they result in clinically apparent infections is an important question. 52 Therefore, we enrolled hospitalized patients with SBP and UTI, which are the most common infections in cirrhosis. 5 Reflecting clinical experience, the yield of causative organisms in UTI was higher than that in SBP on routine culture, and these organisms were consistent with recent literature.…”
Section: Discussionmentioning
confidence: 99%
“…In another cohort of a healthy population, the highest abundance of ARG was TcR ( Hu et al, 2013 ). The ARG abundance difference in different populations may be due to the disease-specific variations in antibiotic resistance under different antibiotic exposures ( Shamsaddini et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rifaximin, a rifamycin antibiotic, was popularly used in travelers’ diarrhea and irritable bowel syndrome. It had been reported to neither affect ARGs nor increase the ARG burden because the use of rifaximin would rarely bring about the development of drug resistance compared with other antibiotics ( Shamsaddini et al, 2021 ). The high ARG burden in CRC patients suggested that it is recommended to consider possible antibiotic resistance when selecting appropriate antibiotic treatments, such as short-term alternating antibiotics and microbiome-based interventions ( Dubinsky et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the technique of sequencing used. A recent study demonstrates significant and profound changes in the microbiota in liver cirrhosis – using metagenomics and not only 16S sequencing – with a favorable effect of rifaximin unlike absorbable antibiotics ( Shamsaddini et al, 2021 ). The extent to which such antibiotic therapies shift individual bile acids in a favorable direction in humans is unclear.…”
Section: Influencing the Intestinementioning
confidence: 99%